FINGER PAINTING PLAY DALAM MENGEMBANGKAN ANAK USIA DINI DI ERA SOCIETY 5.0 - Rahayu, Novita Putri (Universitas Islam Darul Ulum, 2023)
This article is a literature review which aims to find out how useful th helping develop children's fine motor skills. which is in line with Childhood Education Standards (PERMENDIKBUD) (PERMEN concerning Child Development Achievement Standards (STPPA). C small muscles, especially in their hands, will improve with this game. T painting game can help develop children's fine motor skills well and no learn through play, by helping children coordinate hands and eyes, as to hand movements, complex movements, and manipulating moveme and expressing oneself through artistic creation using various media.